The Use of Quizizz in EFL Classroom: Students’ Perceptions and Learning Outcomes at Junior High School - Syahril Nur; Karmila Machmud; Harto Malik; Muziatun; Sartin Miolo (Universitas Islam Negeri Palopo, 2026)
This study aims to examine students’ perceptions and learning outcomes on the use of Quizizz in an English as a Foreign Language (EFL) classroom at MTsN 1 Boalemo. This research employed a mixed-method approach with an explanatory sequential design. The participants were 31 students selected through purposive sampling. Data were collected using a questionnaire, pre-test and post-test, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, N-Gain, paired sample t-test, and Cohen’s d, while qualitative data were analyzed descriptively. The findings revealed that students demonstrated a high level of perception toward the use of Quizizz (M = 3.44), indicating that the platform is useful, engaging, and easy to use. The learning outcomes improved significantly, with the mean score increasing from 62.8 to 81.6 and learning mastery rising from 34% to 87%. The N-Gain score was 0.51 (moderate), the t-test indicated a significant difference (p < 0.05), and the effect size was very large (d = 2.42). The instrument was also proven valid and highly reliable (α = 0.91). However, some challenges were identified, particularly unstable internet connectivity. It can be concluded that Quizizz is an effective tool to enhance students’ engagement and learning outcomes in EFL classrooms.